Study of the effect of external pressure pulsations on the flame - Agafontsev, Mikhail V. (Proceedings of SPIE)
The paper examines the effect of low-amplitude pressure pulsations on the temperature field in the flame formed during methane combustion. Using the Ansys Fluent solver, the fields of temperature, velocity, and other flow characteristics in the presence of internal pressure pulsations were analyzed. As a result of the analysis of the obtained data, qualitative estimates of the effect of pressure pulsations on the flame plume were obtained. It is shown that the effect of acoustic oscillations on the flame plume leads to a change in the rate of combustion of fuel.